Spectators in the Field of Politics - Fitzgerald, Sandey. author. aut Link
IX, 226 p.
Keywords: The book uses the long-standing theatre metaphor to bring political spectators out into the open, finding that they can be politically powerful. Filling out the metaphor with theatre theory, the book also finds that the metaphor can produce a viable model of democratic politics that incorporates spectators in a positive, meaningful way.